Neuroprotective properties of lithium salts during glutamate-induced stress - A. V. Pronin; O. A. Gromova; I. Yu. Torshin; E. V. Stelmashuk; O. P. Aleksandrova; E. E. Genrikhs; L. G. Khaspekov (Неврология, нейропсихиатрия, психосоматика, 2017)
Organic lithium salts are a promising area for searching for effective and safe neuroprotective drugs. By using chronic bilateral common carotid artery occlusion models, the authors have previously found that lithium gluconate and lithium citrate are effective agents to prevent a neurological deficit in brain ischemic or neurodegenerative damages. The use of organic lithium salts in brain ischemia leads to their targeted accumulation in the frontal lobes of the brain and in the cerebrospinal fluid, normalizing trace elemental homeostasis in the brain Objective: to compare the neuroprotective effects of different lithium salts (chloride, carbonate, ascorbate, and citrate).Material and methods. A neurocytological study was performed using a glutamate-induced stress model in cultured granular neurons (CGNs).The state of CGNs was monitored daily and at each experimental stage, by viewing in an inverted phase contrast microscope. The final concentrations of the test substances in the culture medium were 0.1, 0.2, and 0.5, and 1 mM. The survival of CGNs was quantified by directly counting the neurons with intact morphology in 5 fields of vision. Five experiments were carried out for each substance. The number of neurons with intact morphology in the control cultures was taken as 100% survival.Results. Lithium chloride and lithium carbonate in the studied range of concentrations did not show significant neuroprotective properties.Lithium ascorbate and lithium citrate, on the contrary, significantly increased the survival of neurons in mild, moderate and severe glutamateinduced stress. Lithium citrate at a concentration of 0.2 mM increased the survival rate of CGNs by an average of 30% (p < 0.003). The active neuroprotective principles of lithium citrate were shown to be both lithium ion and citrate anion. These positive qualities of the test organic lithium salts are explained primarily by the fact that ascorbate and citrate anions contribute to the enhanced transport of lithium ions into the cells through appropriate ion channels for the transport of organic acids (SLC13A5, etc.).Conclusion. Lithium ascorbate and lithium citrate were confirmed to have an immediate neuroprotective effect on cerebellar CGNs. Treatment of CGNs with lithium citrate showed a 30% increase in cell survival during glutamate-induced stress.